Epigenetic Regulation of Vascular Smooth Muscle Cell Phenotype Switching in Atherosclerotic Artery Remodeling: A Mini-Review - Zurek, Michelle; Aavik, Einari; Mallick, Rahul; Ylä-Herttuala, Seppo (Frontiers in Genetics, 2021)
Atherosclerosis is a chronic inflammatory disease characterized by extensive remodeling of medium and large-sized arteries. Inward remodeling (= lumen shrinkage) of the vascular walls is the underlying cause for ischemia in target organs. Therefore, inward remodeling can be considered the predominant feature of atherosclerotic pathology. Outward remodeling (= lumen enlargement) is a physiological response compensating for lumen shrinkage caused by neointimal hyperplasia, but as a pathological response to changes in blood flow, outward remodeling leads to substantial arterial wall thinning. Thinned vascular walls are prone to rupture, and subsequent thrombus formation accounts for the majority of acute cardiovascular events. Pathological remodeling is driven by inflammatory cells which induce vascular smooth muscle cells to switch from quiescent to a proliferative and migratory phenotype. After decades of intensive research, the molecular mechanisms of arterial remodeling are starting to unfold. In this mini-review, we summarize the current knowledge of the epigenetic and transcriptional regulation of vascular smooth muscle cell phenotype switching from the contractile to the synthetic phenotype involved in arterial remodeling and discuss potential therapeutic options.